COMMUNICATING FOOD TO CHILDREN - Cesiri, Daniela, 1980- Link ([S.l.])
1 online resource
Keywords: This book offers a systematic account of communication on food aimed at children, investigating verbal and visual strategies used in food media in English from synchronic and diachronic perspectives.While there is a wide body of research on food discourse, there has been little to date on children as a particular category of actors within food-related communication. Cesiri integrates work from corpus linguistics, genre analysis, and multimodality to analyze verbal and visual components in media that transmit specialist knowledge and familiarize children with foundational food concepts, the extra-linguistic factors that shape food-related communication, and the ways in which different genres represent culinary traditions to children. The volume features an extensive corpus of technical products such as cookbooks, commercial products such as advertisements, and institutional products such as leaflets from international institutions. In applying a multi-layered perspective to a diverse range of food-related communication materials, Cesiri seeks to unpack whether potential differences in communicative strategies can be attributed to the source culture of interactants or those shared by a specific community of actors, and in turn, further insights into the nature of domain-specific discourse.This volume will appeal to scholars in discourse analysis, multimodality, corpus linguistics, and childhood studies.